Phase I safety and tolerability dose escalation study of microencapsulated hepatocyte intraperitoneal transplantation therapy in adult patients with liver failure: a study protocol - Taihua Yang; Qiang Xia; Zhen Sun; Ping Wan; Lijian Hui; Xiang Yuan; Xinye Zhu; Mei Long; Ludi Zhang (BMJ Open)
Introduction China has a high prevalence of liver diseases, with about 300 million patients suffering from various types of liver diseases, where the incidence of severe liver diseases is 1%–3%. More than half a million people die from end-stage liver disease every year in China. In situ liver transplantation is the most effective treatment for liver failure, but only a limited number of patients undergo liver transplantation due to the shortage of donors. Hepatocyte transplantation requires only a certain number of hepatocytes rather than the whole liver, regardless of complex issues such as in vitro reconstruction of the three-dimensional structure of the liver, blood vessels and biliary ducts, enabling it to be safer and easier to promote in clinical practice than liver transplantation. This study aims to evaluate the safety and tolerability of microencapsulated hepatocyte intraperitoneal transplantation therapy in adult patients with liver failure.Methods and analysis This study is a single-centre, unblinded, single-arm study comprising a dose escalation phase and a preliminary assessment of efficacy. Subjects who were diagnosed with liver failure (including chronic liver failure and acute-on-chronic liver failure), who received 3 days of regular treatment with no beneficial effect and who volunteered to participate in microencapsulated hepatocyte intraperitoneal transplantation therapy will be enrolled. To minimise the number of patients receiving an unbeneficial therapeutic dosage, the accelerated titration design and ‘3+3’ design will be used jointly for the dosage escalation method. All patients with microencapsulated hepatocyte transplantation will be monitored on the 1st, 3rd, 7th, 14th, 28th, 60th and 90th days after the treatment for safety and primary efficacy analyses.Ethics and dissemination Ethical approval has been obtained from the Shanghai Jiao Tong University School of Medicine, Ren Ji Hospital Ethics Committee. Results will be disseminated through publication in a peer-reviewed journal.Trial registration number NCT05727722.